The productivity effects of privatization: Longitudinal estimates from Hungary, Romania, Russia, and Ukraine - J. David Brown; John S. Earle; Almos Telegdy (W.E. Upjohn Institute for Employment Research, 2005)
This paper estimates the effect of privatization on multifactor productivity (MFP) using long panel data for nearly the universe of initially state-owned manufacturing firms in four economies. We exploit the key longitudinal feature of our data to measure and control for preprivatization selection bias and to estimate long-run impacts. We find that the magnitudes of our estimates are robust to alternative functional forms, but sensitive to how we control for selection. Our preferred random growth models imply that majority privatization raises MFP about 15% in Romania, 8% in Hungary, and 2% in Ukraine, while in Russia it lowers it 3%. Privatization to foreign rather than domestic investors has a larger impact, 18-35%, in all countries. Positive domestic effects appear within a year in Hungary, Romania, and Ukraine and continue growing thereafter, but take 5 years after privatization to emerge in Russia.
Keywords: D24; G34; L33; P31; 330; privatization; productivity; foreign ownership; random growth model; transition; Hungary; Romania; Russia; Ukraine; Privatisierung; Produktivität; Verarbeitendes Gewerbe; Rumänien; Ungarn; Ukraine; Russland